Resolución de problemas en los planes de estudio de las universidades formadoras de profesionales en la enseñanza de la matemática en Costa Rica - Araya Vega, Jose Alfredo (2008)
This article summarizes the results of the analysis of the program of the mathematics teaching career from private and state universities, in order to identify whether or not this programs responds as an educational strategy that solves a problem.About it was noted that most of the programs made emphasis that methodological principles for addressing the subject of study, will facilitate the construction and reconstruction of knowledge and profiles of the professional output displayed as a facilitator of the construction and reconstruction of knowledge. Despite the foregoing, with a few exceptions, there is a presence of “Trouble”or as programmatic content or as a curricular or methodological axis. The programs of the mathematics teaching career in Costa Rica are not given appropriate emphasis to the topic of Solving Problems with the importance that for many years has been given at the international level.